Strategi Manajemen Perpustakaan untuk Meningkatkan Layanan Berbasis Literatur Terkini di Perpustakaan Umum Kota Padang - Putri, Sindy Berliana; Marlini, Marlini; Desriyeni, Desriyeni (Lembaga Yasin AlSys, 2026)
Libraries, as institutions that provide information and knowledge, are increasingly required to adapt to technological developments and changing user needs in the digital era. This study aims to examine library management strategies in Indonesia with a focus on strategic planning, human resource management, and key challenges encountered. The method used is a literature review by analyzing various credible sources that discuss library management practices and their development. The findings indicate that well-formulated strategic planning, training and competency development for librarians, and the ability to adapt to information technology are key success factors in library management. However, budget constraints, the shortage of professional librarians, and low public interest in library services remain significant obstacles to optimizing the role of libraries. In conclusion, libraries need to adopt innovative and sustainable strategies to improve service quality, strengthen social relevance, and expand their reach and utilization amid the dynamics of the digital era.